The Adaptive Signal Processing Scheme for Power Quality Conditioning Applications Based on Active Noise Control (ANC) - Han, Yang; Xu, Lin; Yao, Gang; Zhou, Mansoor, Li-Dan; Chen, Chen (Elektronika ir Elektrotechnika, 2009)
The active noise control (ANC) is considered to be the fundamental concept of the adaptive signal processing techniques, which has been increasingly utilized for electric signal decompositions and reconstructions. Followed by an extensive literature survey, this paper aims to provide a systematical theoretical derivation of the ANC problem for power quality conditioning applications. The mathematical formulation of the ANC–based harmonic estimation problem is presented, and the discussion on the mean–square–error (MSE) and misadjustment issues are also reported. The validity and effectiveness of the ANC scheme is verified by the experimental results. Ill. 3, bibl. 24 (in English; abstracts in English, Russian and Lithuanian).